Semantic Function in Mild Cognitive Impairment - Taler, Vanessa; Monetta, Laura; Sheppard, Christine; Ohman, Avery (Frontiers in Psychology, 2020)
It is well-established that semantic deficits are observed in mild cognitive impairment (MCI). However, the extent of impairment in different aspects of semantic function remains unclear, and may be influenced by the tasks used to assess performance. In the present study, people with MCI and cognitively healthy older adults completed a series of tasks assessing lexical access, retrieval, and recognition of semantic information, using different input and output modalities. Control participants outperformed people with MCI in almost all tasks, with the greatest deficits observed in picture naming tasks. This finding is interpreted as reflecting greater deficits in lexical access and/or access to the phonological and orthographic lexicon, and less severe deficits in retrieval and recognition of semantic feature and associative knowledge. In a subset of tasks, relatively greater impairment was also observed in biological compared to man-made items. From a clinical perspective, these results suggest that, while it is preferable that a full semantic battery be included in neuropsychological assessment, in cases where shorter testing time is necessary, picture naming is the task most likely to reveal deficits in people with MCI.